2012
DOI: 10.1007/s00468-012-0676-9
|View full text |Cite
|
Sign up to set email alerts
|

Local seed dispersal in European silver fir (Abies alba Mill.): lessons learned from a seed trap experiment

Abstract: Seed dispersal is an important factor influencing the genetic structure of forest tree populations. Knowledge about the seed shadow is important to assess the ability of tree species to colonize new and disturbed habitats or to respond to environmental change by migrating to more suitable habitats. In a seed trap experiment, we investigated local seed dispersal distances of silver fir seeds (Abies alba Mill.) by explicitly identifying mother trees. For this purpose, we matched microsatellite genotypes of mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 38 publications
4
11
0
3
Order By: Relevance
“…Nonetheless, we found the same spatial pattern of decreasing seed and regeneration density with distance from the edge of the unburned patch, as expected for wind-dispersed species (Nathan & Casagrandi 2004, Nathan & Neeman 2004, Raftoyannis & Spanos 2015. According to Cremer et al (2012), the median distance of seed dispersal of Abies alba, another fir species which like A. cephalonica produces winged seeds dispersed by wind, was 31 m. In our study, more than 70% of the dispersed seeds and young firs were found within a distance shorter than 50m from the parent trees. This is similar to the results of the dispersal curve of most wind-dispersed tree species, which show a peak at, or very close to, the source, followed by a rapid decline, and a long tail (Nathan & Casagrandi 2004, Nathan & Neeman 2004.…”
Section: Discussionsupporting
confidence: 81%
“…Nonetheless, we found the same spatial pattern of decreasing seed and regeneration density with distance from the edge of the unburned patch, as expected for wind-dispersed species (Nathan & Casagrandi 2004, Nathan & Neeman 2004, Raftoyannis & Spanos 2015. According to Cremer et al (2012), the median distance of seed dispersal of Abies alba, another fir species which like A. cephalonica produces winged seeds dispersed by wind, was 31 m. In our study, more than 70% of the dispersed seeds and young firs were found within a distance shorter than 50m from the parent trees. This is similar to the results of the dispersal curve of most wind-dispersed tree species, which show a peak at, or very close to, the source, followed by a rapid decline, and a long tail (Nathan & Casagrandi 2004, Nathan & Neeman 2004.…”
Section: Discussionsupporting
confidence: 81%
“…Insects, fungi, late frost, frost desiccation, and industrial emissions (especially SO 2 ) may also affect the tree (Lingg 1986, Schu¨tt et al 2004, Ellenberg 2009, Kozakova et al 2011. The seed dispersal of A. alba is efficient and comparable to that of other wind-dispersed trees (e.g., Picea abies; Sagnard et al 2007, Szymura et al 2007, Cremer et al 2012. Taproots allow the species to grow on dry locations, for instance, in the Mediterranean region, because they can reach deep-water reserves that accumulate during the wet winter period (Aussenac 2002).…”
Section: Study Object and Areamentioning
confidence: 99%
“…There are a very few papers (Cremer et al 2006, Pawlaczyk et al 2010, Cremer et al 2012, Gömöry et al 2012, Cvrčková et al 2015 describing the variation of silver fir in nuclear microsatellite DNA markers. It is caused by the difficulties in finding polymorphic loci in this taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Another Cremer et al's (2012) study was conducted in the Black Forest, a low mountain range in the southwestern part of Germany. He compared mother trees to seeds on five SSR loci (three the same like in our work) and reported that values of expected and observed heterozygosity and the number of detected allelic richness were as follows: SF 1 (Ho = 0.534, He = 0.539, A R = 5), SF 333 (Ho = 0.489, He = 0.720, A R = 6), and SF b5 (Ho = 0.467, He = 0.471, A R = 7) for forest stands and for seeds: SF 1 (Ho = 0.441, He = 0.509, A R = 7), SF 333 (Ho = 0.557, He = 0.693, A R = 7) and SF b5 (Ho = 0.457, He = 0.529, A R = 8).…”
Section: Discussionmentioning
confidence: 99%